School building experimental characterization in Mediterranean climate regarding comfort, indoor air quality and energy consumption - Barbosa, F. C. (2020)
Public school buildings represent an important share of public buildings in Europe, some of them built several decades ago. In Portugal, there are about 5800 public schools, many of them in free-running conditions, with significant thermal discomfort and without any heating strategy due to economic restrictions. This work studies the Portuguese Brandao school model (from the '70 s), which comprises about 100 non-refurbished basic schools. This paper suggests the passive refurbishment of these public schools with some affordable interventions, regarding the climate features and the reduced capacity to support the operating costs. A prototype classroom was prepared in a Brandao school, in Porto. The in situ experimental campaign consisted of temperature, relative humidity, CO2 concentration and energy consumption measurements. The prototype construction included the improvement of the envelope and of the technical systems. The main goals of this work are: (1) the comparison of the prototype in-service thermal performance in pre-existing conditions and the improvement after the refurbishment in free-running conditions or with some intermittent heating strategies; (2) the establishment of discomfort indexes for the assessment of the discomfort for Mediterranean temperate climate; (3) the quantification of the energy consumption vs discomfort regarding the passive refurbishment strategy and the intermittent heating strategies. When comparing the before and after refurbishment results, the mean daily discomfort indicator has decreased from 34.7 degrees C.hour to 25.2 degrees C.hour in free-running conditions and after the refurbishment has decreased from 25.2 degrees C.hour to 11.9 degrees C.hour for 3 heating hours strategy and to 2.5 degrees C.hour for 10 heating hours strategy. There was an expected increase of CO2 inside the classroom for the corresponding months before and after refurbishment, although the mean CO2 was below the required 1500 ppm. (C) 2020 Elsevier B.V. All rights reserved.